SARS-CoV-2 detection by extraction-free qRT-PCR for massive and rapid COVID-19 diagnosis during a pandemic in Armenia - Avetyan, Diana; Chavushyan, Andranik; Ghazaryan, Hovsep; Melkonyan, Ani; Stepanyan, Ani; Zakharyan, Roksana; Hayrapetyan, Varduhi; Atshemyan, Sofi; Khachatryan, Gisane; Sirunyan, Tamara; Davitavyan, Suren; Martirosyan, Gevorg; et al. (Journal of virological methods, 2021)
•COVID-19 pandemic urges for a rapid and efficient test for infection screening.•Omitting the isolation step enables significant expansion of the testing capacity.•The protocol for COVID-19 qRT-PCR testing on direct swab samples was optimized.•Direct testing has lower sensitivity, but enables testing capacity expansion.•Direct sample sensitivity depends on the transport media type. COVID-19 pandemic severely impacted the healthcare and economy on a global scale. It is widely recognized that mass testing is an efficient way to contain the spread of SARS-CoV-2 infection as well as aid in the development of informed policies for disease management. However, the current COVID-19 worldwide infection rates increased the demand for rapid and reliable screening of infection. We compared the performance of qRT-PCR in direct heat-inactivated (H), heat-inactivated and pelleted (HC) samples against RNA in a group of 74 subjects (44 positive and 30 negative). Then we compared the sensitivity of HC in a larger group of 196 COVID-19 positive samples. Our study suggests that HC samples show higher accuracy for SARS-CoV-2 detection PCR assay compared to direct H (89 % vs 83 % of the detection in RNA). The sensitivity of detection using direct samples varied depending on the sample transport and storage media as well as the viral loads (as measured by qRT-PCR Ct levels). Altogether, all the data suggest that purified RNA provides more accurate results, however, direct sample testing with qRT-PCR may help to significantly increase testing capacity. Switching to the direct sample testing is justified if the number of tests is doubled at least.